Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia. - Alovisi, Mario; Scotti, Nicola; Comba, Allegra; Manzon, Elena; Farina, Elena; Pasqualini, Damiano; Michelotto Tempesta, Riccardo; Breschi, Lorenzo; Cadenaro, Milena (J Prosthodont Res, 2018)
PURPOSE: The aim of this in vitro study was to assess conversion degree (DC), micro-hardness (MH) and bond strength of two dual-curing resin cements employed under translucent monolithic zirconia irradiated with different time protocols. METHODS: 84 square shaped samples of 1mm thickness were prepared from high translucency zirconia blocks and divided into two groups (n=24) according to the cement employed: (1) Rely-X Ultimate; (2) Panavia SA. Each group was further divided into 3 subgroups (n=8) according to the irradiation time: (a) no light; (b) 20s; (c) 120s. Light curing was performed 60s after the sample was placed on the diamond support of a FT-IR spectrophotometer with a high power multiLED lamp. Final DC% were calculated after 10min. After 24h, Vickers Test on the cement layer was performed. The same protocol was used to lute composite cylinders in order to evaluate microshear bond-strength test. ANOVA and Bonferroni tests were performed to find differences between MH and bond-strength to zirconia, while for DC% the Scheirer-Ray-Hare two-way test was used. RESULTS: The two cements reached higher DC% in subgroup (b) and (c). As concern MH, statistics showed an increase in curing time was able to improve MH significantly. Bond-strength was not affected by irradiation time only for Panavia SA. CONCLUSIONS: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.
Keywords: Composite Resins; Dental Bonding; Dental Cements; Hardness; Lansoprazole; Materials Testing; Polymerization; Resins, Synthetic; Spectrophotometry; Time Factors; Zirconium